Meningkatkan Mutu Tenaga Pengajar Profesional Dalam Mewujudkan Tujuan Pendidikan Nasional - Ramlan Ramlan; Farida Isroani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
From a series of laws and government regulations regarding education, educational goals, both regarding educational standards, professional standards for teaching staff, professional teachers must fulfill competence as an absolute requirement, and competence is defined as the unanimity of mastery of the knowledge, skills, and attitudes displayed through performance, in this case there are at least 4 competencies that must be perfectly owned by professional teachers, namely personality competencies (steady, mature, wise, authoritative, wise). Pedagogic Competence (the ability to manage learning, understand students, conditions and environment, the core meaning of the subject). Professional Competence (insightful, mastery of the material, mastery of the substance of teaching materials and so on). Social Competence (social sensitivity, ability to communicate politely, be wise with people around, and so on), the problem in this case in our world of education is whether all teachers are aware of their professional demands? Are teachers continuously evaluating their professionalism as educators and continue to push himself to improve the quality of his profession, how wide the opportunities from the government to teachers to improve their professional quality as teaching staff. If you look at the references to laws, government regulations, ministerial regulations, opportunities to improve the quality of education by improving the teaching profession should continue to be held and widely open to teachers.